Preparation of crosslinked cation exchange membranes by radiation grafting of styrene/divinylbenzene mixtures onto PFA films - Nasef, Mohamed Mahmoud; Saidi, Hamdani (Elsevier Science B.V., 2003)

(untitled)
Crosslinked cation exchange membranes bearing sulfonic acid groups were prepared by radiation-induced grafting of styrene containing 2 and 4% divinylbenzene (DVB) onto poly(tetrafluoroethylene-co-perfluorovinyl ether) (PFA) films followed by sulfonation reactions. The degree of grafting was found to be dependent on the grafting parameters including irradiation time and DVB concentration in the bulk solution. The physico-chemical properties of the membranes such as ion exchange capacity, water uptake and ionic conductivity were evaluated in correlation with the degree of grafting and the level of crosslinking. All the properties of the membranes were found to be functions of the degree of grafting. However, crosslinking of polystyrene grafts with DVB was found to considerably reduce the water uptake and the ionic conductivity of the membranes while showing no effect on the ion exchange capacity. The thermal stability of the membranes represented by desulfonation temperature was found to be independent of crosslinking. Membranes having degrees of grafting of 24% (0% DVB), 24% (2% DVB) and 17% (4% DVB) possess good combinations of physico-chemical properties and can be of practical interest.